Captain cool : the M.S. Dhoni story story - Ezekiel, Gulu; Engineer, Farokh (New Delhi : Westland publication, 2022)
It must be my power, the bat speed I generate, and the swing of the bat...' Mahendra Singh Dhoni is as calm and unruffled a sportsman on the field as he is self-effacing off it. But 'brute strength', 'murderous form' and 'a man possessed' were some of the phrases that came to mind when, on 5 April 2005 in Visakhapatnam, he exploded onto international consciousness by becoming the first regular Indian keeper to score a one-day century. With his striking form on the day, his long locks visible beneath his helmet, red tints glinting in the sunlight, 'Mahi' Dhoni had transformed from a boy hailing from an obscure small town to a sports legend with the aura of a rock star. And yet, Dhoni was no child prodigy, no overnight success. When he made his international debut at 23, he was already mature by Indian cricket standards-with five grinding years of domestic cricket behind him. How that legend came to be-and grew from game to game-is told here by noted sportswriter Gulu Ezekiel in his crackling but measured prose. Captain Cool is the story of MS Dhoni, Indian cricket's poster boy; it is also the heartwarming account of the life of a young man who won India the World Twenty20 in 2007, the 50-over World Cup title in 2011 and the Champions Trophy in 2013, but can still tell his throngs of admirers, 'I am the same boy from Ranchi'
Keywords: Cricket players India Biography; Cricket captains India Biography